Hubungan Dukungan Keluarga dan Pengetahuan Ibu dengan Pantangan Makanan pada Ibu Nifas di Wilayah Kerja Puskesmas Juli Kabupaten Bireuen - Roza, Siska Desta; Sari, Putri Permata (Jurnal Sehat Mandiri, 2023)
Background: Family support is an effective part of the postpartum care process. One of the obstacles that often occurs in society is abstinence from eating after giving birth. After giving birth, a woman needs adequate nutrition to restore her body. This research aims to determine the relationship between family support and maternal knowledge with food restrictions among postpartum mothers in the working area of the Juli Bireuen Regency Public Health Center in 2023. This type of Analytical Survey research uses a Cross Sectional approach. The sampling technique used in this research was total sampling with a population of 38 respondents and a sample of 38 respondents was obtained. This research instrument uses a questionnaire. The research results showed that the majority of mothers had supportive family support, namely 29 people (76.3%). The majority of mothers in the working area of the July Community Health Center had good knowledge, namely 31 mothers (81.6%). Postpartum mothers generally do not abstain from food, namely 23 people (60.5%). Chi square test results p value = 0.001 < α = 0.05. The conclusion is that there is a relationship between family support and maternal knowledge with food restrictions among postpartum mothers in the Juli Health Center working area. Suggestions: It is hoped that the family will provide support and attention to the postpartum mother so that the mother feels loved and wanted, thereby creating good nutrition and a speedy recovery for the mother.